Āryabandhu : Pi.Ke. Bāppuvinṯe jīvacaritṟaṃ - Śrīdharan, Paḷḷiyaṟa, 1949- (Paḷḷiyaṟa Śṟīdharan : distributors, Kaṟanṟ Buks, 1981)
Biography of Āryabandhu (P.K. Bappu), 1887-1978, social reformer from Kerala.